Unraveling the Tourism–Environment–Equity Nexus: A Neighborhood-Scale Analysis of Texas Urban Centers - Omid Mansourihanis; Ayda Zaroujtaghi; Moein Hemmati; Mohammad Javad Maghsoodi Tilaki; Mahdi Alipour (Urban Science)
This study explores the complex interplay between air pollution, the socioeconomic conditions, and the tourism density within Texas’s urban landscapes, focusing on Dallas, Houston, San Antonio, and Austin. Despite extensive research on environmental justice and urban tourism separately, few studies have integrated these fields to examine how tourism development intersects with environmental and socioeconomic disparities at a neighborhood level. This research addresses this gap by employing advanced geospatial analyses and multi-criteria decision analysis to reveal the pronounced clustering of stressed communities on urban peripheries, often removed from tourism’s economic benefits. The study uniquely quantifies the spatial mismatches between tourist hotspots and areas of environmental stress, a dimension often overlooked in the environmental justice literature. Local spatial statistics and cumulative impact analysis uncover statistically significant correlations between high poverty levels and elevated air pollution in specific locales. The results show varying patterns across cities, with Austin presenting the lowest inequality levels and San Antonio exhibiting significant disparities. This granular, neighborhood-centric approach provides novel insights into the tourism–environment–equity nexus, addressing the lack of comprehensive studies linking these factors in rapidly growing Texan metropolitan areas. The findings underscore the critical need for targeted policy interventions and neighborhood-specific approaches in diagnosing urban environmental disparities and crafting equitable urban development policies that consider tourism’s impact on local communities.